GENDER RELATIONS IN ISLAMIC FIQH: THE QUEST FOR EQUALITY AND JUSTICE - Rakhmawati Rakhmawati (SHIBGHAH: Journal of Muslim Societies, 2019)
The issue of gender relations is an important agenda of all parties, because the reality of gender differences that implicates the differences in status, roles and responsibilities between men  women often cause what is called gender injustice or discrimination and oppression. This injustice can occur in various fields of life, both within domestic and public areas, in the fields of education, health, security, economy, politics, and broader development. This problem of gender injustice in many cases becomes an issue that is quite sensitive and not easily solved, especially when related to the religious doctrine, or even as if getting theological legitimacy. The main purpose of this study is to search the understanding and origin of gender and answer why gender construction is at issue. The next discussion will analyze at a glance the root causes of understanding gender-biased in religion. This research focuses on how to form good relations between men and women to complement each other in order to create cooperation in the family and community; therefore, it ends injustice between the two in accordance with principles the Qur'an and Hadith, also it is the importance to demand equality in order to obtain the same rights where women and men could collaborate to solve problems.